Application of anthocyanin as a color indicator in gelatin films - Saroat Rawdkuen (2020)
© 2020 Elsevier Ltd Anthocyanin extracts from different plants were used to develop intelligent gelatin films. Red cabbage, sweet potatoes, roselle, butterfly pea, husks, and peelings from mangosteen and red dragon fruit were used. Anthocyanin extracted from butterfly pea had the highest pH sensitivity, which suggested that the distinct color change at each pH. The intelligent gelatin films were prepared using a casting method from gelatin, glycerol, butterfly pea anthocyanin (BPA) extracts, or resazurin, at pH 6. The thickness of the films ranged between 43 and 48 μm. Significant decreases for tensile strength (7.0–2.4 MPa) and water vapor permeability (8.4–2.4 ×10-11 g m m-2 s-1 Pa-1) were observed when adding BPA extract (P < 0.05). The gelatin film with BPA extracts was dark blue, while the film with resazurin was violet/purple. The control film had a smooth surface that was compact without any porous structures when observed using a scanning electron microscope. The film with BPA extracts showed the highest antioxidant activity and showed greater pH sensitivity as compared to the film with resazurin, which suggested that changes in the films’ color occurred at different pH levels. Therefore, the film with BPA extracts was considered a promising film for intelligent packaging. This film used for packaging will serve as an effective pH indicator for the consumer. However, further investigation of its performance is necessary before its application is used in real food systems.